Dynamics of cumulating of metronidazole in the gut wall on a model of mechanical ileus. - V. V. Nepomniashchyi; T. I. Tamm; D. P. Polianskyi; O. A. Shakalova; O. P. Zakharchuk (Medičnì Perspektivi)
The frequency of acute intestinal obstruction in relation to urgent surgical diseases in Ukraine remains high and reaches 3.8-6%. In the postoperative period, such patients develop a high number of severe purulent-septic complications. For the prevention and treatment of purulent-septic complications, various combinations of antibiotics with metronidazole are used. On the model of experimental mechanical ileus, the ability of the modified bowel wall to retain metronidazole was determined. The experiment was performed on 20 lines of the "Vistar" line in which the mechanical model of the ileus was formed. The results of the study showed that the accumulation of metronidazole in the phlegmonous-altered gut wall at therapeutic concentrations occurs within the first 24 hours and is of a short-term nature. The lack of the possibility of cumulating of antibacterial drugs by the wall of the inflamed gut after 24 hours contributes to the development of purulent complications.